Determinants of Complete Basic Immunization Achievement in West Sumatra Province (Analysis of SKI 2023) - Fauzi, Falah; Gusti, Aria; Pradipta, Yudi; Masrizal, Masrizal (UNIVERSITAS ALIFAH PADANG, 2026)
Background: Complete basic immunization (CBI) coverage in West Sumatra Province remains critically low, posing a significant public health challenge. Objective: This study aimed to identify determinants of CBI achievement among children aged 12–23 months in West Sumatra Province using nationally representative data from the 2023 Indonesia Health Survey (Survei Kesehatan Indonesia/SKI 2023).Methods: A cross-sectional study design was employed through secondary data analysis of the SKI 2023 dataset. The analytical sample comprised 609 children aged 12–23 months residing in West Sumatra Province. Variables examined included child characteristics (sex, birth weight), maternal factors (employment status, educational level, gestational age at delivery, KIA book ownership), health service factors (place of delivery, healthcare accessibility), family socioeconomic status, and history of adverse events following immunization (AEFI). Survey-weighted univariate, bivariate (chi-square test), and multivariate (binary logistic regression) analyses were performed. Statistical significance was set at p < 0.05.Results: Among 609 children aged 12–23 months, 87.8% (n = 534) had incomplete immunization status and only 12.2% (n = 75) had received complete basic immunization. The measles-rubella vaccine recorded the lowest coverage at 68.4%. In bivariate analysis, maternal employment (p = 0.045) and KIA book ownership (p = 0.001) were significantly associated with CBI status. In multivariate analysis, only KIA book ownership remained a significant independent determinant: children whose mothers did not own a KIA book were nearly five times more likely to have incomplete immunization (Adjusted OR = 4.86; 95% CI: 1.63–14.47; p = 0.005).Conclusion: KIA book ownership is the primary independent determinant of complete basic immunization achievement in West Sumatra Province. Targeted interventions should prioritize optimizing KIA book utilization, strengthening health education for working mothers, and addressing structural barriers to immunization services.